Preparation of Ag NWs and Ag NWs@PDMS stretchable sensors based on rapid polyol method and semi-dry process - Li, Wei; He, Yin; Xu, Jie; Wang, Wen-yu; Zhu, Zheng-tao; Liu, Hao (Journal of alloys and compounds, 2019)
The silver nanowires (Ag NWs) prepared by improved polyol method in 30min were applied to the stretchable strain sensors. Three factors affecting the morphology of Ag NWs were discussed, including reaction temperature, molecular weight of PVP, ratio of silver nitrate (AgNO3) and polyvinyl pyrrolidone (PVP). Experimental results showed that Ag NWs with diameter of 53 ± 9 nm, length of 31 ± 7 μm and the aspect ratio is 584.9 were obtained under the optimum conditions. Thus, a new and convenient method was proposed to fabricate flexible stretchable sensors by embed Ag NWs into Polydimethylsiloxane (PDMS). The stability, hysteresis, and sensitivity of the Ag NWs@PDMS strain sensors were evaluated by cyclic stretch-release test. Our strain sensor with good stability, higher sensitivity (the gauge factor is 4.11) and good repeatability could be stretched 10% continuously for about 200 cycles. Ag NWs@PDMS flexible sensors can be used in wearable devices to monitor human movements. [Display omitted] •The effects of different conditions on the morphology of silver nanowires were discussed based on the rapid polyol method.•We propose a novel method to prepare Ag NWs@PDMS flexible stretching sensor.•The sensitivity, hysteresis and repeatability of the sensor are studied.•Ag NWs@PDMS flexible sensors are assembled at the knees to monitor human movement.